Le rôle des journées juridiques et administratives franco-croates (2007-2017) - Massot, Jean (Array, 2018)
The subject of this paper is a memoir of the last ten years of Croatian – French administrative days. Accordingly, without just limiting this exclusively to the hrestomaty of Administrative Days, published during the Ten Days, we will focus on the comments, suggestions and criticisms related to three elements: topics and presentation methods, presenters and moderators of round tables and the audience. Finally, we would like to remember all the organizers in the successful organisation of the commendable Croatian -French administrative days.